2021
DOI: 10.3390/rs13163110
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Port Construction on the Spatial Pattern of Land Use in Coastal Zones Based on CLDI and LUT Models: A Case Study of Qingdao and Yantai

Abstract: Ports are an important type of land use in coastal cities, and the development of ports has a significant influence on the spatial pattern of land use in port cities. However, the research focusing on economic indicators hardly reflects the process of changes in the spatial distribution of land development in coastal port cities. This paper introduces a spatial association rule method to establish a coastline and land development intensity (CLDI) model and land use transfer (LUT) model in the vertical directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…By accounting for maritime knowledge flows in the delimitation of the coastal zone, we deepen our understanding of coastalization and enhance the methods of its registration. The traditional delimitation of the coastal zone (and coastalization) done by measuring the geographical proximity to the sea of human settlements [14,17] or the clustering of economic activity [15,16], could now be combined with an assessment of functions performed by entities. The extended understanding of the coastal economy was previously verified by Morrissey and O'Donoghue [22], who have mapped the inland communication within a maritime economic network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By accounting for maritime knowledge flows in the delimitation of the coastal zone, we deepen our understanding of coastalization and enhance the methods of its registration. The traditional delimitation of the coastal zone (and coastalization) done by measuring the geographical proximity to the sea of human settlements [14,17] or the clustering of economic activity [15,16], could now be combined with an assessment of functions performed by entities. The extended understanding of the coastal economy was previously verified by Morrissey and O'Donoghue [22], who have mapped the inland communication within a maritime economic network.…”
Section: Discussionmentioning
confidence: 99%
“…Current perspectives on defining the boundaries of the coastal zone are based on an assessment of natural and environmental factors (e.g. land elevation) [13], migration processes and settlement structure [14], the location of port infrastructure [15], industrial facilities [16], etc. The range of propagation of the coastalization effect may vary depending on the country, including both local zones up to 1 km, and coastal areas up to 10, 50, 150 and even 200 km [17].…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity analyses from certain selected ports worldwide clearly indicated that the growth of ports unerringly boost the country's economy with signi cant negative impact to the natural environ post their construction. For instance, Qingdao and Yantai ports in China showed pre and post port development from sea to land with enhanced constructions and replacement of cultivation and forest areas to development infrastructures (Yan et al, 2021). Sydney harbour in Australia was reported for prominent coastal area developments and infrastructures (Mayer-Pinto et al, 2015).…”
Section: Determination Of Impact In Uence Of Lulc Features Using Ahpmentioning
confidence: 99%
“…Mundra, Hazira, Karaikal, Krishnapatnam, Gangavaram and Gopalpur ports along the Indian coast have been selected to understand the impact of port intervention on their coastal environment. This paper utilized Remote Sensing and GIS techniques to assess historic and periodic Land use/ Land cover changes (Yan et al, 2021). Also, the manuscript discusses sediment quantity dynamics along the port area using numerical model simulations.…”
Section: Introductionmentioning
confidence: 99%
“…We divided the study area into 33 buffer zones starting at the northernmost end of the basin and made 1 km spaced buffers to the south (Figure 1). We drew on the buffer zone gradient strip method [40]. The 33 buffer zones were divided into different gradients, such as suburban Guiyang, the county town, suburbs of the county town, and the countryside, from north to south according to the study basin location conditions.…”
Section: Buffer Scalementioning
confidence: 99%